High performance porous iron oxide-carbon nanotube nanocomposite as an anode material for lithium-ion batteries - Lin, Q.; Wang, J.; Zhong, Y.; Sunarso, J.; Tadé, M.; Li, L.; Shao, Zongping (Pergamon, 2016)
Here, we showed that relatively high content of Fe3O4 nanoparticles (up to 83 wt. %) can be homogeneously dispersed into carbon nanotubes (CNTs) conductive networks using non-aqueous media by refluxing method. Three different Fe3O4-CNTs composites were prepared, i.e., Fe3O4-CNTs-50, Fe3O4-CNTs-80 and Fe3O4-CNTs-90 that contain increasing amount of Fe3O4 from 50 wt. % to 83 wt. % and to 89 wt. %. These composites have higher surface area and higher pore volume than Fe3O4 component due to CNTs content. The best composite, i.e., Fe3O4-CNTs-80 demonstrated negligible capacity loss up to 100 cycles and high discharge capacity of 930 mA h g−1 at 100th cycle and 100 mA g−1 current discharge rate. This composite also exhibited excellent rate capability where up to the 78.8% of original capacity can be retained at high current discharge rate of 1000 mA g−1. These performances were enabled by a unique porous architecture based on homogenous dispersion of Fe3O4 nanoparticles into CNTs networks that leads to short Li+ diffusion path, high electric conductivity and buffering space to accommodate large volume change of Fe3O4 component during the charge-discharge processes.